Optimization of Electrical Properties of MoS2 Field‐Effect Transistors by Dipole Layer Coulombic Interaction With Trap States. Issue 7 (27th March 2019) - Chuai, Xichen; Yang, Guanhua; Wei, Wei; Wang, Jiawei; Shi, Xuewen; Lu, Congyan; Zhao, Ying; Su, Yue; Wu, Quantan; Geng, Di; Lu, Nianduan; Li, Ling; et al.
Abstract : The large negative threshold voltage is one of major electrical factors hindering potential applications of MoS2 transistors in low‐power circuit systems. Here, a strategy by forming an electric dipole layer on the surface of MoS2 is presented to optimize the threshold voltage in monolayer polycrystalline MoS2 field‐effect transistors. The electric dipole in an inert non‐conjugated polymer, perfluoropolyether (PFPE), can interact with trapped electrons in the MoS2 active layer and transfer the traps from shallow into deep states, which remarkably improves the threshold voltage. Otherwise, ab initio calculation and molecular dynamics simulation are employed to investigate the transport properties of MoS2 with PFPE. The calculated results imply that localized electrons are dominantly affected by PFPE, while free electrons are irrelevant. This method with dipole layer provides a pathway to implementation of high‐performance MoS2 transistors for future electronic applications. Abstract : Employing a polymer material with electric dipole moment, i.e. perfluoropolyether, the electrical properties of MoS2 field‐effect transistors including threshold voltage and subthreshold swings are successfully optimized with invariability of mobility. This effect, which is attributed to the Coulombic interaction between electric dipole and localized charge, is proved by ab initio calculation and molecular dynamics simulation.